Incidental carcinoma of gallbladder following laparoscopic cholecystectomy: A single center study - Shrestha, Santosh; Sharma, Deepak; Ghimire, Roshan; Maharjan, Dhiresh Kumar; Thapa, Prabin Bikram (Grande Medical Journal, 2020)
Background: Gallbladder adenocarcinoma is the most common malignant tumor of the biliary tract. Most of gall bladder cancers are detected incidentally only after pathological examination of the excised surgical specimens. In this study we investigated the characteristics of incidental gallbladder cancers in our center. Material & methods: We retrospectively reviewed all of the cholecystectomy specimens in sent for histopathology following laparoscopic cholecystectomy in the study period from January 2015 to October 2019. Clinicopathological characteristics were extracted from the patients' clinical charts, which included symptoms, radiological findings, laboratory data, and surgical procedures as well as outcome.Results: We identified 6 cases of incidental gall bladder cancer, consisting of 4 women and 2 men ranging in age from 28 to 77 years (mean age 60.5 after pathological study of 1530 resected gall bladders. Out of the 6 cases, 1 case was carcinoma in situ of gall bladder, 1 was T1b  and other 4 cases were T2 carcinoma.Conclusions: The rate of incidental gallbladder carcinoma in our study was 0.39%. This lower incidence could in part be due to increasing use of routine laparoscopic cholecystectomy for symptomatic gallbladder. This strategy of increased early intervention further adds to the advantage of higher chances of gallbladder cancer detection in early stages, and thus better prognosis.